Trends and challenges in the management of sport organizations: Perspectives in Colombia - Cardona Mejía, LA.; Cardona Ramírez, S. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
This study aimed to recognize trends and challenges in the management of public and private sport organizations in Colombia. We realized a theoretical analysis from the literature around the subject and a content analysis with information provided in a panel of recognized experts in the area. The results indicate innovation, the incorporation of information and communication technologies, the organizational change management, the need to strengthen the training profiles of managers, inter-institutional relations and networking, as some of the most challenging important for managers. It is a starting point for the design of plans in organizations and plans of training for managers.